2005
DOI: 10.1080/13880200590963222
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Properties of the Ethanol Root Extract ofCissampelos mucronata.

Abstract: The study was undertaken to investigate the antiulcer properties of the ethanol root extract of Cissampelos mucronata A. Rich (Menispermaceae). Three models of experimental ulcer induction in rats were employed in the study. Oral median lethal dose (LD 50 ) was determined in mice using Lorke's method, and the isolated tissue preparations were used to investigate the effect of the extract on calcium ion mobilization in the ileum and H 2 -receptor blocking property in nongravid rat uterine strip. Study of the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Early induction of labor (Lampiao et al, 2018); Congo: snake bite (Chifundera, 1987); Ethiopia: constipation, diarrhea, painful menstruation, sterility/impotence, amebiase, pain during lactation, renal diseases (Lulekal et al, 2008), weakness and unstoppable shaking (Flatie et al, 2009); anthelmintic, provokes diarrhea (Tolossa et al, 2013), wound healing (Paulos et al, 2016); Kenya: wounds (Kokwaro, 1987), malaria (Muthaura et al, 2007); Madagascar: induces vomiting (Daruty, 1886); Nigeria: malaria, ulcers, stomachache (Katasayal et al, 2015); Sudan: malaria, infarct, stomachache, magic (El-Kamali, 2009); Tanzania: snake bite, poisoning, stomachache (Ruffo, 1991); Uganda: children nourishment (Adjanohoun et al, 1993) Antimalarial (Muthaura et al, 2015;Tshibangu et al, 2002, Gessler et al, 1995, antibacterial and larvicidal (Nondo et al, 2011), antimalarial (not confirmed;Benoit-Vical et al, 2008), antidiabetic (Tanko et al, 2007, antiulcer (Nwafor et al, 2005), antimicrobial (Tchibangu et al, 2002) Cryptolepis oblongifolia Benin/Zambia: gonorrhoea; Mozambique: malaria, Tanzania/Zimbabwe: cough, stomachache, diarrhea in children, aphrodisiac; Zambia: wounds (Bosch, 2011)…”
Section: Cissampelos Mucronatamentioning
confidence: 99%
“…Early induction of labor (Lampiao et al, 2018); Congo: snake bite (Chifundera, 1987); Ethiopia: constipation, diarrhea, painful menstruation, sterility/impotence, amebiase, pain during lactation, renal diseases (Lulekal et al, 2008), weakness and unstoppable shaking (Flatie et al, 2009); anthelmintic, provokes diarrhea (Tolossa et al, 2013), wound healing (Paulos et al, 2016); Kenya: wounds (Kokwaro, 1987), malaria (Muthaura et al, 2007); Madagascar: induces vomiting (Daruty, 1886); Nigeria: malaria, ulcers, stomachache (Katasayal et al, 2015); Sudan: malaria, infarct, stomachache, magic (El-Kamali, 2009); Tanzania: snake bite, poisoning, stomachache (Ruffo, 1991); Uganda: children nourishment (Adjanohoun et al, 1993) Antimalarial (Muthaura et al, 2015;Tshibangu et al, 2002, Gessler et al, 1995, antibacterial and larvicidal (Nondo et al, 2011), antimalarial (not confirmed;Benoit-Vical et al, 2008), antidiabetic (Tanko et al, 2007, antiulcer (Nwafor et al, 2005), antimicrobial (Tchibangu et al, 2002) Cryptolepis oblongifolia Benin/Zambia: gonorrhoea; Mozambique: malaria, Tanzania/Zimbabwe: cough, stomachache, diarrhea in children, aphrodisiac; Zambia: wounds (Bosch, 2011)…”
Section: Cissampelos Mucronatamentioning
confidence: 99%
“…The treatment of peptic ulcers with plant products used in folk medicine and the protection of induced gastric ulcer in laboratory animals using medicinal plants was well documented (Disi et al, 1998). There are avalanche of scientific support on the efficacy of medicinal plants in the management of ulcers of different aetiologies (Austin and Jegadeesan, 2000;Akah et al, 2001;Nwafor and Akah, 2003;Nwafor and Okoye, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…and the average taken as mean ulcer index for each group. [19][20][21] The degree of ulcer protection for each treatment group was calculated as a percentage for the mean ulcer index of the negative control group. 22 Acid neutralizing capacity The acid neutralizing capacity value for MECP (500, 1000, 1500 and 2000 mg/5 mL) was compared with the standard antacid Danacid [Aluminium hydroxide (250 mg) + Magnesium hydroxide (120 mg)/5 mL].…”
Section: Measurement Of Ulcer Indexmentioning
confidence: 99%